The Representation of Fantasy Comedy in Movie Posters Entitled Turning Red Using Semiotics Theory - Diah Anggraeni, Alifania; Hellystia, Devi (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2022)
This research aims to identify the representation of fantasy comedy and explain the sign system to represent the fantasy comedy that is found in Turning Red movie posters. This research was descriptive qualitative because the result was discussed descriptively. The data of this research was the signifier and signifier, verbal signs represented by the text which consists of words, phrases, clauses, and sentences on the posters, and the non-verbal signs represented by the picture. Then, the color meaning of fantasy comedy in the Turning Red movie posters. From this research, we can understand the representation of fantasy comedy about the signifier and signified using Ferdinand de Saussure's semiotics theory, and the analysis of verbal and non-verbal signs using Gillian Dyer's theory in the movie posters. Then, the analysis of the color meaning using Sean Adams' theory. The findings show that this research found 98 data which are presented in three points. The first is the signifier and signified with 28 data, the second is verbal signs with 14 data, and the non-verbal signs with 44 data. The third is the color meanings with 12 data in the Turning Red movie posters.